Reconfigurable negative bit line collapsed supply write-assist for 9T-ST static random access memory cell - Chokkakula Ganesh; Fazal Noorbasha; Korlapati Satyanarayana Murthy (Institute of Advanced Engineering and Science, 2023)
This paper presents a reconfigurable negative bit line collapsed supply (RNBLCS) write driver circuit for the 9T Schmitt trigger-based static random-access memory (SRAM) cell (9T-ST), significantly improving write performance for real-time memory applications. In deep sub-micron technology, increasing device parameter deviations significantly reduce SRAM cells' write-ability. The proposed RNBLCS write-assist driver for 9T-ST SRAM cell has 0.84×, 0.48×, 0.27× optimized write access delay and 1.05×, 1.08×, 1.19× improvement in write static noise margin (WSNM), 1.05×, 1.13×, and 1.39× improvement in write margin (WM), 0.96×, 0.89× and 0.72× minimum write trip-point (WTP) from transient-negative bit line (Tran-NBL), capacitive charge sharing (CCS), and conventional write circuits respectively. The proposed RNBLCS is functionally verified using a synopsys custom compiler with a 16 nm BSIM4 model card for bulk complementary metal-oxide semiconductor (CMOS).